Building organizational resilience in Malaysian food and beverages industry: Scale development and validation - Baharuddin, Nur Farhah; Wan Omar, Wan Marhaini (Journal of Islamic, Social, Economics and Development, 2025)
The COVID-19 pandemic has compelled organisations to explore new ways of managing work and the environment. The dynamics of resilience in adopting digital technology have become increasingly important in the face of various challenges, including natural disasters, terrorism, economic recessions, mass migration, cyber threats, and other socio-political and economic trends. This study aims to develop an instrument and empirically validate the measurement of the organizational resilience dimensions. The instrument was developed through a structured process, starting with the identification of organizational resilience dimensions, item generation, questionnaire development, pre-testing, pilot testing, and scale validation. Six industry experts and three academic experts were involved in the pre-test phase to assess the instrument's content. In the phase of pilot test, data were collected from 100 SMEs in the food and beverage industry located on the East Coast of Malaysia. The reliability and validity of the instrument were assessed through Cronbach’s Alpha and Exploratory Factor Analysis (EFA). The final framework comprises of four dimensions that were modelled as independent variables; dynamic capability, marketing agility capability, strategic flexibility, and relative advantage, with organizational resilience as the dependent variable. Consequently, a reliable measurement tool for organizational resilience was established and empirically validated prior to conducting the main survey. This tool can support businesses in identifying their strengths and weaknesses, guiding them toward long-term sustainability and competitiveness. The instrument is expected to assist future researchers and SMEs in assessing and enhancing organisational resilience in dynamic environments.